CO1 Amplicon Sequence Variants of bulk arthropod samples (mild lysis) collected with Malaise traps from the Insect Biome Atlas project in Madagascar - Andreia Miraldo; John Sundh; Elzbieta Iwaszkiewicz-Eggebrecht; Emma Granqvist; Lokeshwaran Manoharan; Piotr Łukasik; Ayco J. M. Tack; Anders F. Andersson; Tomas Roslin; Fredrik Ronquist (Swedish Museum of Natural History, 2025)
Amplicon Sequence Variants of 418bp of CO1 from mild lysed arthropod community samples collected with Malaise traps from the Insect Biome Atlas project (https://www.insectbiomeatlas.org/) in Sweden, as described in the IBA data paper (https://doi.org/10.1038/s41597-025-05151-0) .

This dataset was published via the SBDI ASV portal (https://asv-portal.biodiversitydata.se/) , and has been updated from 'Metadata only' to 'Occurrence' type.

Occurrence data were compiled from the following IBA Figshare items:

Processed ASV data from the Insect Biome Atlas Project v3: (https://figshare.scilifelab.se/articles/dataset/Processed_ASV_data_from_the_Insect_Biome_Atlas_Project/27202368/3)

- cleaned_noise_filtered_cluster_taxonomy_MG.tsv.gz (https://figshare.scilifelab.se/ndownloader/files/50067522)
- spikeins_tax_MG.tsv.gz (https://figshare.scilifelab.se/ndownloader/files/50067525)


Amplicon sequence variants from the Insect Biome Atlas project v6: (https://figshare.scilifelab.se/articles/dataset/Amplicon_sequence_variants_from_the_Insect_Biome_Atlas_project/25480681/6)

- CO1_asv_counts_MG.tsv.gz (https://figshare.scilifelab.se/ndownloader/files/%2049727829)
- CO1_asv_seqs_MG.fasta.gz (https://figshare.scilifelab.se/ndownloader/files/46381135)


The following samples were excluded from this resource due to sequencing failure: P26762_1247, P26762_1333, P27359_1207, P27361_1307, P27361_1148; or lack of non-zero counts for annotated ASVs: P27359_2998, P27361_1125, P27360_1032.
Keywords: Metadata; Observation; OCCURRENCE; Biological Sciences; Biologi